CUE USAGE IN VOLLEYBALL: A TIME COURSE COMPARISON OF ELITE, INTERMEDIATE AND NOVICE FEMALE PLAYERS - Vansteenkiste, P; Vaeyens, R; Zeuwts, L; Philippaerts, R; Lenoir, M (Biology of Sport, 2014)
This study compared visual search strategies in adult female volleyball players of three levels. Video clips of the attack of the opponent team were presented on a large screen and participants reacted to the final pass before the spike. Reaction time, response accuracy and eye movement patterns were measured. Elite players had the highest response accuracy (97.50 ± 3.5%) compared to the intermediate (91.50 ± 4.7%) and novice players (83.50 ± 17.6%; p<0.05). Novices had a remarkably high range of reaction time but no significant differences were found in comparison to the reaction time of elite and intermediate players. In general, the three groups showed similar gaze behaviour with the apparent use of visual pivots at moments of reception and final pass. This confirms the holistic model of image perception for volleyball and suggests that expert players extract more information from parafoveal regions.